(3TQM GdMGhj GdUZjQs - (3YdGA GdOjf CHh GdMSf Ydj Hf ESeGYjd Hf jhSa GdJHQjRi Gdbhfhi GdTGaYjs; (3YHO GdZaGQ Hf YHO GdcQje Hf YHO GdZaGQ GdbRhjfj, fLe GdOjf,J (B665 (3g` s ((3TjQGR s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bhdg (B: (3HGH JUM hUjI GdMQ Edi BNQg EYde Cf GdcJGH hGdSfI hGdELeGY eJYGVOI Ydi LhGR GdhUjI s
(3BNQgG (B:s
(3bhdg (B: (3hjDLQ hddSjO Cf jDLQ eSJhdOJg hjSJNOegG hjWCgG dCfg eGdcgG heGdc efGaYgG ZjQ Cfg eefhg ef HjYgG dJCcO Mb GdYJb ajgG hdg Cf jRhLgG CjVkG hGddg CYde HGdUhGH gPG BNQ TQM Gdbhfhi hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQSJ ddeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdTGaYjs